Analysis of tax relief measures as a result of the covid-19 pandemic in south africa, compared with the tax measures of other members of the brics group - Selemela, Elsie (University of the Witswatersrand, Johannesburg, 2023)
The purpose of this report is to analyse tax relief measures that were taken as a result of the COVID-19 outbreak in South Africa, evaluate the approach taken and compare it with other countries in the BRICS international organisation. The COVID-19 pandemic caused numerous company closures and employment losses (IMF, 2020). Governments worldwide had to intervene to support their citizens and keep businesses afloat (IMF, 2020). In order to maintain widespread access to essential goods and services, taxation is crucial (IMF, 2020). The dire effect on economic activities around the world influenced tax laws (IMF, 2020). It fell to tax administrators to ease the tax burden on taxpayers as they were facing hardships (OECD [Organisation for Economic Co operations and Development], 2020). The International Monetary Fund (IMF) states that the design of tax systems can help stabilise economies when faced with crisis (IMF, 2020). The South African government implemented tax relief measures because of COVID-19, although taxpayers are still experiencing the detrimental effects of COVID-19. It is the government’s wish to offer additional help to businesses and individuals who are still facing these hardships and also assist in rebuilding businesses (SARS, 2021). This report will look at tax measures that were taken by South Africa in comparison to those that were taken by Brazil, Russia, India and China to determine the usefulness of these measures in dealing with the effects of COVID-19 on taxes. Some measures were introduced for a short time and therefore are no longer applicable, but it is important to consider them in this report because they might have long-term effects on taxes. The findings of this analysis indicate which measures were used, when they were implemented, and how taxes in the BRICS countries changed while adjusting to COVID-19. It was found that tax policies put in place in South Africa were unjustified since they decreased tax collection without any measures in place to boost it (IMF, 2020). Examining what other BRICS nations were doing to increase tax collection during the COVID-19 outbreak can help identify areas for improvement.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation).
Keywords: UCTD; BRICS; COVID-19 pandemic; Income tax rates; OECD; South Africa’s tax relief measures; Tax maxims; SDG-8: Decent work and economic growth